Tracing the intrusion of fossil carbon into coastal Louisiana macrofauna using natural 14C and 13C abundances. (July 2016) - Wilson, Rachel M.; Cherrier, Jennifer; Sarkodee-Adoo, Judith; Bosman, Samantha; Mickle, Alejandra; Chanton, Jeffrey P.
Abstract: The Deepwater Horizon oil spill released a large volume of 13 C and radiocarbon depleted organic matter to the northern Gulf of Mexico. Evidence of petroleum-derived carbon entering the offshore planktonic foodweb, as well as widespread oiling of coastal areas documented in previous studies suggests that hydrocarbons could have entered the near shore foodweb. To test this hypothesis, we measured radiocarbon ( Δ 14 C%) and stable carbon isotopes ( δ 13 C) in an assortment of fish tissue, invertebrate tissue and shell samples collected within a year of the spill at seven sites from Louisiana to Florida USA across the northern Gulf of Mexico. We observed a west–east gradient with the most depleted radiocarbon values found in Terrebonne Bay, Louisana and increasingly enriched radiocarbon values in organisms collected at sites to the east. Depleted radiocarbon values as low as −10% in invertebrate soft tissue from Terrebonne suggest assimilation of fossil carbon (2.8±1.2%), consistent with the hypothesis that organic matter from petrochemical reservoirs released during the Deepwater Horizon spill entered the coastal food web to a limited extent. Further there was a significant correlation between radiocarbon and δ 13 C values in invertebrate tissue consistent with this hypothesis. Both oyster tissue and hard head catfish tissue collected in impacted areas of coastal Louisiana were significantly depleted in 14 C and 13 C relative to organisms collected in the unaffected Apalachicola Bay, Florida ( p <0.014). Alternative explanations for these results include the influence of chronic hydrocarbon pollution along the western gulf coast or that the organisms ingest carbon derived from 14 C depleted organic matter mobilized during the erosion of coastal marshes in southern Louisiana.